Eclipta prostrata (L.) L. (asteraceae) – new species for the flora of Republic of Moldova [Articol] - Cassir, Polina; Izverscaia, Tatiana; Ghendov, Veaceslav (CEP USM, 2023)
The article presents data on the new vascular plant species Eclipta prostrata (L.) L. (=Eclipta alba (L.) Hassk.), belonging to the Asteraceae family, in the spontaneous flora of the Republic of Moldova. Populations of this new species were recorded in the south of the republic, on the territory of the Ramsar site ,,Lower Prut Lakes”. Synonymy, chorology, stationary characteristics, photographic images, black and white diagnostic illustrations are presented, as well as some useful plant properties.

În articol sunt prezentate date despre noua specie de plante vasculare Eclipta prostrata (L.) L. (=Eclipta alba (L.) Hassk.), aparținând familiei Asteraceae, în flora spontană a Republicii Moldova. Populațiile acestei specii noi au fost înregistrate în sudul republicii, pe teritoriul sitului Ramsar „Lacurile Prutului de Jos”. Sunt prezentate sinonimia, corologia, caracteristicile staționale, imaginile foto, ilustrațiile diagnostice alb-negru, precum și câteva proprietăți utile ale plantei.
Eclipta prostrata (L.) L. (asteraceae) – specie nouă pentru flora Republicii Moldova
Keywords: vascular flora; Eclipta prostrata; Ramsar site ,,Lower Prut Lakes”; Republic of Moldova; flora vasculară; Eclipta prostrata; Situl Ramsar,,Lacurile Prutului de Jos”; Republica Moldova